Unraveling the genomic reorganization of polygalacturonase-inhibiting proteins in chickpea - Ellur, Vishnutej; Wei, Wei; Ghogare‬, Rishikesh; Solanki, Shyam; Vandemark, George; Brueggeman, Robert; Chen, Weidong (Frontiers in Genetics, 2023)
Polygalacturonase-inhibiting proteins (PGIPs) are cell wall proteins that inhibit pathogen polygalacturonases (PGs). PGIPs, like other defense-related proteins, contain extracellular leucine-rich repeats (eLRRs), which are required for pathogen PG recognition. The importance of these PGIPs in plant defense has been well documented. This study focuses on chickpea (Cicer arietinum) PGIPs (CaPGIPs) owing to the limited information available on this important crop. This study identified two novel CaPGIPs (CaPGIP3 and CaPGIP4) and computationally characterized all four CaPGIPs in the gene family, including the previously reported CaPGIP1 and CaPGIP2. The findings suggest that CaPGIP1, CaPGIP3, and CaPGIP4 proteins possess N-terminal signal peptides, ten LRRs, theoretical molecular mass, and isoelectric points comparable to other legume PGIPs. Phylogenetic analysis and multiple sequence alignment revealed that the CaPGIP1, CaPGIP3, and CaPGIP4 amino acid sequences are similar to the other PGIPs reported in legumes. In addition, several cis-acting elements that are typical of pathogen response, tissue-specific activity, hormone response, and abiotic stress-related are present in the promoters of CaPGIP1, CaPGIP3, and CaPGIP4 genes. Localization experiments showed that CaPGIP1, CaPGIP3, and CaPGIP4 are located in the cell wall or membrane. Transcript levels of CaPGIP1, CaPGIP3, and CaPGIP4 genes analyzed at untreated conditions show varied expression patterns analogous to other defense-related gene families. Interestingly, CaPGIP2 lacked a signal peptide, more than half of the LRRs, and other characteristics of a typical PGIP and subcellular localization indicated it is not located in the cell wall or membrane. The study’s findings demonstrate CaPGIP1, CaPGIP3, and CaPGIP4’s similarity to other legume PGIPs and suggest they might possess the potential to combat chickpea pathogens.